Impact of Rapeseed and Soy Lecithin on Postprandial Lipid Metabolism, Bile Acid Profile, and Gut Bacteria in Mice. Issue 9 (29th April 2021) - Robert, Chloé; Buisson, Charline; Laugerette, Fabienne; Abrous, Hélène; Rainteau, Dominique; Humbert, Lydie; Vande Weghe, Justine; Meugnier, Emmanuelle; Loizon, Emmanuelle; Caillet, François; Van Dorsselaer, Benjamin; Urdaci, Maria; et al.
Abstract : Scope: Synthetic emulsifiers have recently been shown to promote metabolic syndrome and considerably alter gut microbiota. Yet, data are lacking regarding the effects of natural emulsifiers, such as plant lecithins rich in essential α‐linolenic acid (ALA), on gut and metabolic health. Methods and Results: For 5 days, male Swiss mice are fed diets containing similar amounts of ALA and 0, 1, 3, or 10% rapeseed lecithin (RL) or 10% soy lecithin (SL). Following an overnight fast, they are force‐fed the same oil mixture and euthanized after 90 minutes. The consumption of lecithin significantly increased fecal levels of the Clostridium leptum group ( p = 0.0004), regardless of origin or dose, without altering hepatic or intestinal expression of genes of lipid metabolism. 10%‐RL increased ALA abundance in plasma triacylglycerols at 90 minutes, reduced cecal bile acid hydrophobicity, and increased their sulfatation, as demonstrated by the increased hepatic RNA expression of Sult2a1 ( p = 0.037) and cecal cholic acid‐7 sulfate (CA‐7S) concentration ( p = 0.05) versus 0%‐lecithin. Conclusion: After only 5 days, nutritional doses of RL and SL modified gut bacteria in mice, by specifically increasing C. leptum group. RL also increased postprandial ALA abundance and induced beneficial modifications of the bile acid profile. ALA‐rich lecithins, especially RL, may then appear as promising natural emulsifiers. Abstract : Plant lecithins are the major natural emulsifiers used in food, yet data is lacking regarding their effects on metabolic health. We reveal that, in mice, the short‐term consumption of nutritional doses of rapeseed and soy lecithin increase the fecal abundance of a health‐promoting bacteria, without modifying lipid metabolism. Rapeseed lecithin induces beneficial changes to the bile acid pool and enhances plasma concentration of an essential ω‐3. Rapeseed lecithin appears as a promising alternative to synthetic emulsifiers.